Web development of staff attendance and salary management system for Taska Rizqin Ceria Cemerlang - Mustafa, Maisarah (2019)
The most basic thing when it comes to managing employees, is to record the attendance and from the attendance record, an integrated payroll can be produced. This is the reason why companies who understand the importance of managing employee have attendance system to keep track the performance of employees and having a salary management system to help speed up the calculation. This is why this project is aimed to develop a web-based system that can record the employee’s attendance and from the attendance record, a payslip can be generated as the calculation of the salary is being automated by the system. Previously, this organization used manual system to record attendance and calculates salary making it difficult to generate a report. The target audience is all employees who worked for Taska Rizqin Ceria Cemerlang. Features for attendance system includes log in and log out, clock in and out using a button to record the time, application for absence by filling up a form and a dashboard for admin. For salary management system, the feature include are an automated salary calculation. The limitations of this project are the language used is Bahasa Melayu and it does not support attendance system that needs to use a specific device. This project used System Development Life Cycle (SDLC) as the methodology which only covers from planning phase until the testing phase. After the system is completely developed, a testing session has been conducted. From the testing most of the users are satisfied, but there are a few improvements that can be done. For example, adding a feature where it can detect the current location of the staff when she clock-in and out and integrate with other tools like a fingerprint scanner. For future recommendation, this project may use fingerprint, smart card or QR barcode to record the attendance. Overall, it may be said that this project is needed to record and manage employee’s salary and attendance so that the management of the nursery can go more smoothly.